G329 Modelling the potential impact of new out-of-hospital (OOH) models of care on paediatric emergency department (ED) presentations. (24th May 2017) - Viner, RM; Blackburn, F; White, F; Nelson, S; Parr, T; Cleugh, F; Lemer, C; Watson, M; Hargreaves, D
Abstract : Aims: A major component of better integrated care is improving urgent care for children and young people(CYP). However few data are available to guide commissioners/providers in planning OOH models to reduce ED presentations. Methods: Prospective data collection on sequential CYP <18 years presenting to 6 busy EDs across London 10am– 10pm over 14 days(Feb–March 2016). We used a supernumerary clinician to collect data on diagnosis, severity and clinical need for investigations and management. We used algorithms based on clinical need to identify patients potentially appropriately managed in a range of new OOH models. Models were identified from literature and service review(see Table). Results: We obtained data on 3020 CYP (mean age 6.1 year; 0–17.9 years). 95.6% were in segments considered appropriate for the OOH models: transient acute illness, exacerbation of LTC, complex LTC/disability and injury/trauma. 81.9% were either not ill/injured or only mildly ill/injured. Most required assessment by a clinician with skills in assessing illness (39.6%) or injuries (30.9%), with only 2.1% requiring a specialist paediatric opinion and 6.8% requiring other specialists. The Table shows the potential proportions appropriate for management within each OOH model. Conclusions: New OOH models could have managed 14%–76% of observed paediatric ED presentations. While enhancement of current primary care could potentially manage around one-quarter of ED presentations, an enhanced CYP service across a GP confederation might manage 45% and more comprehensive services could potentially manage 65%–75% of current ED presentations.